The Dynamics Of Entrepreneurial Motivation Among Women: A Comparative Study Of Businesswomen In Saudi Arabia And Bahrain - Muhammad A. Sadi, Muhammad A. Sadi; M. Al-Ghazali, Basheer (Asian Academy of Management (AAM), 2012)
This study explores the underlying dynamics of motivation for women entrepreneurs in Saudi Arabia and Bahrain, using t-test and ANOVA analyses. Various distinct motivational factors were found in both countries. Self-achievement was the most prominent factor motivating Saudi women to start their own businesses. However, for Bahraini women, the profit motive was the most prominent motivational factor.